In Situ Formed Protective Barrier Enabled by Sulfur@Titanium Carbide (MXene) Ink for Achieving High‐Capacity, Long Lifetime Li‐S Batteries. Issue 9 (4th July 2018) - Tang, Huan; Li, Wenlong; Pan, Limei; Cullen, Conor P.; Liu, Yu; Pakdel, Amir; Long, Donghui; Yang, Jian; McEvoy, Niall; Duesberg, Georg S.; Nicolosi, Valeria; Zhang, Chuanfang (John)
Abstract: Sulfur (S) is an attractive cathode material with advantages including high theoretical capacity and low cost. However, issues such as the lithium polysulfide shuttle effect and its insulating properties greatly limit the future applications of lithium‐sulfur (Li‐S) batteries. Here, a viscous aqueous ink with nanoscale S uniformly decorated on the polar, metallically conductive titanium carbide MXene nanosheets (S@Ti3 C2 T x ) is reported to address these issues. Importantly, it is observed that the conductive Ti3 C2 T x mediator efficiently chemisorbs the soluble polysulfides and converts them into thiosulfate/sulfate. The in situ formed sulfate complex layer acts as a thick protective barrier, which significantly retards the shuttling of polysulfides upon cycling and improves the sulfur utilization. Consequently, the binder‐free, robust, highly electrically conductive composite film exhibits outstanding electrochemical performance, including high capacities (1244–1350 mAh g ‐1 ), excellent rate handling, and impressive cycling stability (0.035–0.048% capacity loss per cycle), surpassing the best MXene‐S batteries known. The fabrication of a pouch cell based on the freestanding S@Ti3 C2 T x film is also reported. The prototype device showcases high capacities and excellent mechanical flexibility. Considering the broad family of MXenes and their unique roles in immobilizing the polysulfides, various S@MXene composites can be similarly fabricated with promising Li + storage capability and long lifetime performance. Abstract : A viscous S@titanium carbide MXene ink and in‐situ formed protective barrier are demonstrated. The polar, conductive MXene mediator efficiently chemisorbs the soluble polysulfides and converts them into a thiosulfate/sulfate layer, which significantly retards the polysulfides shuttle upon cycling and improves the S utilization. Consequently, the robust freestanding electrode demonstrates high capacities, excellent rate capability, and cycling stability.